Movement Disorders on YouTube — Caveat Spectator - Stamelou, Maria; Fung, Victor S.C; Bhatia, Kailash P; Tijssen, Marina A.J; Espay, Alberto J; Lang, Anthony E; Hallett, Mark; Edwards, Mark J (The New England journal of medicine, 2011)
Seven neurologists independently reviewed YouTube videos of patients described as having dystonia, Parkinsonism, chorea, myoclonus, tics, or tremor. These experts rated 19 of 29 popular videos as actually showing psychogenic movement disorders rather the conditions listed. To the Editor: For many patients and their families, the Internet has become the primary resource for medical information, in addition to providing a forum for patients to share their personal experiences. Movement disorders, which include Parkinson's disease, dystonia, and tremor, are common neurologic conditions that readily lend themselves to demonstration by video. We were recently alerted by our patients to content regarding movement disorders that is available on YouTube (www.youtube.com), the third most visited Web site. 1 However, a brief search revealed that many of the videos seemed to us to be atypical for the specific form of movement disorder . . .